OPTIMALISASI LITERASI DAN NUMERASI SISWA SEKOLAH DASAR MELALUI PROGRAM BIMBINGAN BELAJAR DI DESA BALAROA KABUPATEN TOLITOLI - Anjela Jenista Tuku; Muh. Khaerul Ummah BK; Hamna Hamna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
The low literacy and numeracy skills of elementary school students in Balaroa Village pose a challenge to improving the quality of education. This community service program aims to enhance students' literacy and numeracy skills through routine and structured tutoring activities. The method used is a qualitative approach with an action study. The subjects in this activity are elementary school students in lower and upper grades who experience difficulties in reading, writing, and arithmetic. The tutoring activities are conducted twice weekly for two months, with materials tailored to the students' needs. The results of the activities indicate an increase in reading comprehension, simple writing, and basic arithmetic skills. In addition, students demonstrated increased learning motivation and self-confidence in solving literacy and numeracy problems. Tutoring has proven effective as an after-school support strategy in helping students overcome learning difficulties. This program has also received a positive response from local parents and teachers. Thus, tutoring can be an alternative solution to improve students' basic skills in areas with limited access to additional education.